Analysis of Profitability in Good Agriculture Practices Based Vegetable Farming System in Mid-hill Region of Nepal - Kharel, Menila; Raut, Nani; Dahal, Bed Mani (Nepalese Horticulture, 2024)
Implementing Good Agriculture Practices (GAP) impacts both the economic viability and sustainability of vegetable production. Since income significantly influences farmers' decisions to adopt GAP, understanding the profitability of following GAP is crucial for facilitating the transition from non-GAP to GAP. This study aimed to assess the profitability of GAP farms compared to non-GAP farms in three districts of the Kathmandu Valley: Kathmandu, Lalitpur and Bhaktapur. Altogether six farms, one GAP and one non-GAP farms from each district, were selected purposively. The GAP farms selected for this study were following GAP for more than five years. Primary data on farm characteristics were collected through pre-designed interview questionnaire. Profitability analysis of the selected farms was conducted using the Benefit-Cost Ratio (BCR). The farm characteristics showed that GAP farms prioritized reducing chemical fertilizers and pesticides, while non-GAP farms relied heavily on chemical inputs. The BCR revealed that despite higher fixed and variable costs in GAP farms higher gross and net returns were observed in these farms. The GAP farms were more profitable and sustainable compared to non-GAP farms in all three districts. The highest BCR of 1.52 was observed in the GAP farm in Kathmandu, followed by 1.41 in the GAP farm in Lalitpur, and 1.23 in the GAP farm in Bhaktapur. In contrast, lower BCRs were found in non-GAP farms: 1.04 in Bhaktapur, 0.95 in Kathmandu, and 0.72 in Lalitpur, indicating a loss in the latter two farms.